Perbandingan Fenomena Seksual dalam Novel Dadaisme Karya Dewi Sartika dan Novel Imipramine Karya Nova Riyanti Yusuf - Ramaina, Fatra; Asri, Yasnur; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was (1) to describe the forms of sexual phenomena, (2) the elements of fiction that builds sexual phenomena, (3) the factors that cause sexual phenomenon, and (4) the similarities and differences in sexual phenomena Dadaisme masterpiece novel by Dewi Sartika Imipramine novel work of Nova Ryanti Joseph. The data of this study the form of words. Data were collected by using phase read, understand and record the forms and elements of fiction that builds on the phenomenon of sexual characters in the novel, as well as an inventory of the data in the format of the inventory data. The findings of the study in both novels are (1) the forms of the phenomenon of sexual intercourse that is legally married, sexual relations between men and women outside of marriage, adultery, incest, homosexuality and masturbation, (2) the elements of fiction that builds phenomenon namely sexual monologues and dialogues of the characters, (3) factors contributing to the phenomenon of the sexual and psychological environmental factors, (4) similarity of sexual phenomena, namely sex husband wives, sex between men and women outside marriage, infidelity and differences sexual phenomena, namely incest, homosexuality, masturbation.